2016
DOI: 10.1089/cyber.2015.0169
|View full text |Cite
|
Sign up to set email alerts
|

“What Are You Thinking When You Look at Me?” A Pilot Study of the Use of Virtual Reality in Body Image

Abstract: Body image disturbance (BID) is implicated in the etiology, maintenance, and relapse of the eating disorders, and remains challenging to treat. New paradigms such as virtual reality (VR) may offer an ecologically viable method to assess and treat BID. This pilot study aimed to determine if a VR environment could elicit increased BID in a nonclinical group of women who were dieting due to body image concerns or nonclinical women who were not dieting. Forty-one nonclinical females participated in the VR paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Studies on eating disorders included those on body image disturbance (BID) [ 65 , 66 ], anorexia, and bulimia nervosa [ 36 , 67 ]. Gutiérrez-Maldonado et al [ 67 ] compared this form of VR with a more immersive VR that used the Oculus Rift Developers Kit 1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on eating disorders included those on body image disturbance (BID) [ 65 , 66 ], anorexia, and bulimia nervosa [ 36 , 67 ]. Gutiérrez-Maldonado et al [ 67 ] compared this form of VR with a more immersive VR that used the Oculus Rift Developers Kit 1.…”
Section: Resultsmentioning
confidence: 99%
“…Derleme çalışmalar, kontrol grupsuz deneysel çalışmalar, randomize kontrollü çalışmalar hatta son dönemde meta analiz çalışmaları bu alandaki çalışmalara örnektir. SG uygulamaları post travmatik stres bozukluğu, [6][7][8][9][10] obsesif kompulsif bozukluk, [11][12][13] alkol kötüye kullanımı, [14] yeme bozuklukları ve beden imajı ile ilgili problemler [15,16] ve şizofreni [17,18] gibi birçok alanda kullanılmaktadır. SG uygulamaları bu çalışmalarda zaman zaman bir müdahale yöntemi, zaman zaman bir tanı koyabilme aracı olarak kullanılmıştır.…”
Section: Sanal Gerçeklik (Sg) Uygulamalarının Psikolojik Yardım Alanıunclassified
“…These varied from body image disturbance (BID) [58,59], anorexia and bulimia nervosa [55][56][60][61], food cravings [57] and obesity [62]. VR's visual ability to induce cravings led to specific virtual reality craving exposure therapy (VRCET) being the most common form of intervention [55,57,63].…”
Section: Eating Disordersmentioning
confidence: 99%
“…Mountford et al [59] concluded that dieters reported higher social evaluative concerns compared to non-dieters. Purvis et al [58] found women reported higher levels of body satisfaction in a VR environment compared to control conditions.…”
Section: Eating Disordersmentioning
confidence: 99%